Periodontal condition is associated with adverse perinatal outcomes and premature rupture of membranes in low-income pregnant women in Bogota, Colombia: a case–control study (2020)
Objectives: To assess the periodontal condition as a factor associated with adverse perinatal outcomes, premature rupture of membranes (PRM), and preeclampsia in low-income pregnant women treated at public hospitals in Bogotá, Colombia. Methods: Pregnant women with preterm birth (PTB) and low birth weight (LBW) or both conditions (n = 107/428), or only PTB (n = 73/292) or LBW (n = 74/296) or with PRM (n = 98/392) or preeclampsia (n = 76/304) in a ratio of four controls for each case, coming from three hospitals of the public Northern Network of Bogotá, Colombia were studied. Sociodemographic, perinatal adverse outcome history, antenatal care, chronic infections, periodontal condition, threatened abortion, bleeding in the second half of pregnancy, oligohydramnios, diabetes, gestational diabetes, alcohol consumption, hypertension, smoking, alcohol during pregnancy were determined. Logistic regression was conducted to establish factors associated to perinatal adverse outcomes. Multiple correspondence analysis was conducted as secondary analysis. Results: Threatened abortion, absence of antenatal care, hypertension, chronic infections, and periodontal condition were the most important factors associated with perinatal adverse outcomes. The presence of periodontal pockets was associated with LBW OR 2.52 (IC95% 1.36–4.70), PTB OR 2.04 (IC95% 1.10–3.64), PTB-LBW or both OR 2.08 (IC95% 1.18–3.31), PRM OR 2.04 (IC95% 1.17–3.56). Periodontal pockets presence was not associated with preeclampsia. Multiple correspondence analyses showed high correlation between PRM with chronic infection and presence of periodontal pockets. Conclusions: Periodontal condition is a factor independent of other important risk factors for a perinatal adverse outcome and PRM. Prevention of periodontal disease should be included in preconception and prenatal care programs.